2014
DOI: 10.1155/2014/849020
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Metallic Foreign Body inside the Knee Medial Femoral Condyle

Abstract: Foreign bodies in the knee joint are uncommon, particularly those not related to surgical procedures. In this paper, we present a case of an intraosseous metallic foreign body situated in the medial femoral condyle for one year, causing pain, which was removed with complete resolution of the symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Arthroscopy has been recognized as an efficient means for foreign bodies removal from the stifle joint in human surgery. 5,[8][9][10][11][12]14,23 Multiple attempts to arthroscopically remove a broken tip of a curette from an elbow joint failed in a dog. 7 The fragment then migrated into the radial fossa of the humeral condyle and was left in situ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthroscopy has been recognized as an efficient means for foreign bodies removal from the stifle joint in human surgery. 5,[8][9][10][11][12]14,23 Multiple attempts to arthroscopically remove a broken tip of a curette from an elbow joint failed in a dog. 7 The fragment then migrated into the radial fossa of the humeral condyle and was left in situ.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of joint foreign bodies caused by penetration of the skin or after arthroscopy in both human or veterinary medicine. [1][2][3][4][5][6][7][8][9][10] Stifle joints arthroscopic removal of bullets, metal fragments, needles, glass and plastic objects have been reported. 3,5,[10][11][12] When being lodged intra-articular, foreign bodies can cause lesions of the cartilage, menisci or ligaments.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign bodies in knee joints are rare. Authors reported an intraosseous metallic foreign body in the lateral [88] and medial [89] condyles of the femur associated with pain in the left knee. Low radiopaque objects are usually missed on imaging investigations.…”
Section: Foreign Bodymentioning
confidence: 99%
“…Foreign body in the knee following occupational injuries [ 1 ], war injuries [ 2 , 3 ], prick injuries [ 4 , 5 ] and intra articular injection [ 6 ] have been described in the literature. These reported foreign bodies have embedded in the soft tissues of the knee or the bone.…”
Section: Introductionmentioning
confidence: 99%
“… Careful and thorough clinical evaluation after creating a good rapport with the child is of utmost importance to find the initial insult. The usefulness of Radiographs and Computed tomography are limited in this condition [ 1 ]. Arthroscopic retrieval of foreign body and synovectomy would have reduced the postoperative morbidity.…”
mentioning
confidence: 99%